Review paperCholesterol-lowering therapy and cell membranes. Stable plaque at the expense of unstable membranes? - Wainwright, Glyn; Mascitelli, Luca; Goldstein, Mark R. (Archives of Medical Science, 2009)
Current guidelines encourage ambitious long term cholesterol lowering with statins, in order to decrease cardiovascular disease events. However, by regulating the biosynthesis of cholesterol we potentially change the form and function of every cell membrane from the head to the toe. As research into cell morphology and membrane function realises more dependencies upon cholesterol rich lipid membranes, our clinical understanding of long term inhibition of cholesterol biosynthesis is also changing. This review of non-cardiovascular research concerning such membrane effects raises important new issues concerning the clinical advantages and disadvantages of the long term use, and broadening criteria, of cholesterol reductions.